1997
DOI: 10.1046/j.1570-7458.1997.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect feeding on cucumber mediated by rhizobacteria‐induced plant resistance

Abstract: Select strains of plant growth-promoting rhizobacteria (PGPR) were evaluated in greenhouse experiments with cucumber for induction of resistance against cucumber beetle (Diabrotica undecimpunctata howardi Barber) feeding and the beetle-transmitted cucurbit wilt disease. When beetles were given a choice between PGPR-treated and nontreated cucumber, their feeding on stems and cotyledons and the severity of wilt symptoms were significantly lower on PGPR-treated plants. HPLC analysis demonstrated that cotyledons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 19 publications
2
31
0
4
Order By: Relevance
“…However, the larval mortality was high in endosulfan treatment where the emerging adults were absent. Similar results were obtained by Zehnder et al (1997aZehnder et al ( , 1997b wherein the PGPR treated cucumber plants showed reduced consumption by cucumber beetles with reduction in the percentage of wilted vines both in the glasshouse and field experiments. The altered feeding behaviour of the insects was due to reduction in the palatability.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, the larval mortality was high in endosulfan treatment where the emerging adults were absent. Similar results were obtained by Zehnder et al (1997aZehnder et al ( , 1997b wherein the PGPR treated cucumber plants showed reduced consumption by cucumber beetles with reduction in the percentage of wilted vines both in the glasshouse and field experiments. The altered feeding behaviour of the insects was due to reduction in the palatability.…”
Section: Discussionsupporting
confidence: 84%
“…Chestnut sprayed with P. fluorescens resulted in 20% weevil mortality (Yaman et al 1999). Biological control of pests using bacteria has been demonstrated by several other researchers (Fahey et al 1991;Racke and Sikora 1992;Zehnder et al 1997aZehnder et al , 1997bRajendran 2003). Reduction in consumption of boll tissues of cotton treated with bioformulation of Bacillus by H. armigera has been observed (Bhuvaneswari 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results indicate that rhizobacteria-mediated ISR, like SAR, is effective against multiple diseases. Moreover, two recent reports describe that cucumber plants growing from PGPR-treated seeds in the field supported lower numbers of the spotted cucumber beetle, Diabrotica undecimpunctata, and the striped cucumber beetle, Acalymna vittatum (110,111). PGPR treatment resulted in greater beetle control than did weekly applications of insecticide.…”
Section: Absence Of a Typical Dose-response Correlation Known For Toxmentioning
confidence: 96%
“…Knowing that the bacterial wilt pathogen, Erwinia tracheiphila (Smith), is vectored by cucumber beetles (Agrios, 1978, Yao et al, 1996, the Auburn workers conducted greenhouse and laboratory experiments to determine whether PGPR-mediated protection against bacterial wilt resulted from ISR against the pathogen, the vector, or both (Zehnder et al, 1997b). Results showed that attenuated beetle feeding on PGPR-treated cucumber was associated with reduced concentrations of cucurbitacin, a secondary plant compound and cucumber beetle feeding stimulant.…”
Section: December 2002mentioning
confidence: 99%